Rethinking Bullying Prevention in Early Childhood Education: Holistic and Participatory Pedagogies - Nurul Afrianti; Nadiya Kurniati; Erhamwilda; Fitroh Hayati; Huriah Rachmah; Nabilah Nur'aini (UPT Publikasi Ilmiah (Universitas Islam Bandung), 2026)
Abstract.Bullying in early childhood is seen as a relational and ecological issue, influenced by emotional regulation, classroom climate, social participation, family, and culture. This review examines how holistic and participatory pedagogies help prevent bullying, based on research from 2009-2025 in Indonesia and internationally, covering development psychology, social-emotional learning, trauma-informed education, and ecological approaches. Six key themes emerge: bullying as a relational-ecological issue, social-emotional learning as prevention, participatory and democratic learning, trauma-informed classrooms, family and community partnerships, and playful interventions. Prevention is most effective when environments foster emotional safety, empathy, cooperation, child agency, and inclusion. These approaches work together by addressing developmental skills and social structures that sustain exclusion. The review notes limitations like vague definitions, limited long-term studies, and inadequate non-Western context adaptation. It advocates moving from reactive discipline to relational, ecological, and community-based strategies, with implications for curriculum, teacher training, family involvement, and policy.